A periphery hindered strategy with a dopant and sensitizer for solution-processed red TSF-OLEDs with high color purity. Issue 13 (7th March 2022) - Zhao, Guimin; Zhou, Renyin; Zhang, Guanghao; Chen, Haowen; Ma, Daiyu; Tian, Wenwen; Jiang, Wei; Sun, Yueming
Abstract : A peripheral protection strategy to obtain a TADF sensitizer and a conventional fluorescent dopant achieved suppressive intermolecular quenching and an efficient FET process, allowing solution-processed red TSF OLEDs with high color purity. Abstract : Red fluorescent dyes with high color purity are indispensable for ultrahigh definition displays. However, general methods for constructing red luminophores require extended conjugate lengths or strong charge transfer, resulting in large non-radiative components and wide emission spectra. Hence, in this work, a red fluorochrome, 5tbuph-bodipy, was devised and synthesized through a strategy of periphery hindering involving steric tert -butyl units to weaken intermolecular interactions and improve emission efficiency in the solid state. To maximize the utilization of excitons, a novel dendritic thermally activated delayed fluorescence (TADF) sensitizer, phCz-4CzTPN, was also designed to facilitate efficient Förster energy transfer (FET) from the singlet of the TADF sensitizer to that of a conventional fluorescent dopant (CFD, 5tbuph-bodipy ), inhibiting intermolecular interactions and improving solubility during the solution process. Through analyzing the photophysical and kinetic parameters of thermally activated delayed fluorescence-sensitized fluorescent (TSF) materials, the efficiency of the FET process was confirmed. As a result, solution-processed red devices showed a maximum external quantum efficiency (EQEmax ) value, CIE coordinates, and a small full width at half maximum height of 4.9%, (0.64, 0.36), and 47 nm, respectively. This work provides a novel molecular design strategy to explore more narrowband CFDs and TADF sensitizers. Furthermore, the potential of TADF dendrimers as sensitizers was revealed in solution-processed red TSF devices.